Elemental [videorecording (Blu-Ray + DVD)] - Sohn, Peter; Hoberg, John; Likkel, Kat (Kathryn Anne), 1962-; Hsueh, Brenda; Newman, Thomas, 1955- (Disney, 2023)
In Element City, Fire, Water, Land and Air residents live together. Ember is a tough, quick-witted, and fiery young woman, whose friendship with a fun, sappy, go-with-the-flow guy named Wade challenges her beliefs about the world they live in.